Nanometer‐Scale Uniform Conductance Switching in Molecular Memristors. Issue 42 (6th September 2020) - Goswami, Sreetosh; Deb, Debalina; Tempez, Agnès; Chaigneau, Marc; Rath, Santi Prasad; Lal, Manohar; Ariando,; Williams, R. Stanley; Goswami, Sreebrata; Venkatesan, Thirumalai
Abstract: One common challenge highlighted in almost every review article on organic resistive memory is the lack of areal switching uniformity. This, in fact, is a puzzle because a molecular switching mechanism should ideally be isotropic and produce homogeneous current switching free from electroforming. Such a demonstration, however, remains elusive to date. The reports attempting to characterize a nanoscopic picture of switching in molecular films show random current spikes, just opposite to the expectation. Here, this longstanding conundrum is resolved by demonstrating 100% spatially homogeneous current switching (driven by molecular redox) in memristors based on Ru‐complexes of azo‐aromatic ligands. Through a concurrent nanoscopic spatial mapping using conductive atomic force microscopy and in operando tip‐enhanced Raman spectroscopy (both with resolution <7 nm),  it is shown that molecular switching in the films is uniform from hundreds of micrometers down to the nanoscale and that conductance value exactly correlates with spectroscopically determined molecular redox states. This provides a deterministic molecular route to obtain spatially homogeneous, forming‐free switching that can conceivably overcome the chronic problems of robustness, consistency, reproducibility, and scalability in organic memristors. Abstract : A well‐known problem of all the existing resistive‐switching mechanisms is that they are inherently nonuniform and suffer from stochastic variability. This long‐standing problem is resolved by demonstrating a 100% areally uniform current switching driven by molecular redox, characterized via concurrent conductive atomic force microscopy and tip‐enhanced Raman spectroscopy with <7 nm resolution.